Migration and return in modern African literature : black bodies in white spaces - Cole, Ernest, 1965- (Rochester : University of Rochester Press, 2025)
"Using close readings of nine novels by African or African-descended novelists, this book examines three phases of African migration: departure, disillusionment, and the impulse to return. The experiences of African migrants in the diaspora are deeply inflected by the condition of living as Black bodies in white spaces. In this work, author Ernest Cole examines closely the narratives of migration and return presented in nine powerful novels by authors who include Chimamanda Andichie, NoViolet Bulawayo, Teju Cole, and others. The novels reveal a reversal of expectations that migrants from Africa experience upon arrival in the West, a reversal prompted in part by the racial prejudice they are confronted with as Black individuals. As the author notes, the novels also illustrate the desire to return to the homeland as a better alternative to the precarious life in the West, even though such a move is not without its complications. The study is divided into two parts with seven chapters. The first three chapters deal with the novels' depictions of migrants' experiences in the West and the last four focus on the journey home. Collectively, the chapters lay out three phases in the migration process: departure from home, disillusionment in the West, and return to the country of origin. Within this framework, the book uses displacement and dislocation to examine a host of themes-social alienation, alterity, and the precarity of Africans in the diaspora"--
Reasons for departure -- Unfulfilled dreams -- Disillusionment and death -- Psychological depression -- Challenges to reintegration -- The new hybridity -- Constructive liminality.
Includes bibliographical references (pages 209-216) and index.
Keywords: African fiction (English) -- History and criticism; Emigration and immigration in literature; Immigrants in literature; Black people in literature